Opportunities for Organ Donor Intervention Research: Saving Lives by Improving the Quality and Quantity of Organs for Transplantation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The organ donation and transplantation system strives to honor the gift of donated organs by fully using those organs to save and improve the quality of the lives of their recipients. However, there are not enough donated organs to meet the demand and some donated organs may not be recovered, some recovered organs may not be transplanted, and some transplanted organs may not function adequately.
Keywords: Health and Medicine

Building a National Capability to Monitor and Assess Medical Countermeasure Use During a Public Health Emergency: Going Beyond the Last Mile: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
During public health emergencies (PHEs) involving chemical, biological, radiological, or nuclear threats or emerging infectious diseases, medical countermeasures (MCMs) (e.g., drugs, vaccines, devices) may need to be dispensed or administered to affected populations to help mitigate the human health impact of the threat. The optimal MCMs determined for use during an emergency might be U.S. Food and Drug Administration (FDA) approved but used in unapproved ways (e.g., in a new age group or against a new agent); FDA approved using animal models because human efficacy testing is not ethical or feasible; or not yet FDA approved for any indication.
Keywords: Health and Medicine